Trademark Protection Regulations for MSMEs in Advancing an Equitable Creative Economy - Anis Mashdurohatun; Tri Atika Febriany; Jentung Wisnu Murti; Seftia Azrianti; Mustafa Khedewi (Contrarius Indonesia, 2026)
Trademark protection for Micro, Small, and Medium Enterprises (MSMEs) is essential to ensuring legal certainty, enhancing business competitiveness, and fostering an equitable creative economy. However, Indonesia's current trademark legal framework remains insufficiently responsive to the distinctive needs and characteristics of MSMEs. This study aims to examine the shortcomings of the current trademark protection framework applicable to MSMEs and to formulate an ideal regulatory model capable of supporting the development of an equitable creative economy. Adopting a socio-legal research method with statutory and conceptual approaches, this study finds that trademark protection for MSMEs remains inadequate due to the implementation of the first to file principle, the absence of affirmative legal protection, weak institutional coordination, limited access to legal assistance, and the ineffectiveness of trademark infringement enforcement mechanisms in the digital era. Accordingly, reconstruction of the trademark protection framework is necessary through a justice oriented regulatory model that integrates affirmative protection for MSMEs, institutional strengthening, and digital law enforcement in order to ensure legal certainty, substantive justice, and sustainable economic development.